Sketsa Dakwah dan Pembinaan Qur'ani Masyarakat Desa Mangeloreng Melalui KKN STIBA Makassar - Ariesman Ariesman (WAHATUL MUJTAMA': Jurnal Pengabdian Masyarakat, 2020)
Malerongeng Village is an area with a relatively strong level of religiosity. Religious culture, preserving the zikkiri tradition 'to the point that religious leaders are the most prominent in this village. The purpose of the STIBA Makassar Class III Real Work Lecture (KKN) is as a form of community service which is a pillar of the tri dharma of higher education. The method of implementing community service in the Mangeloreng Village begins with mapping the problems and needs of the community by using instruments that are made independently combined with SOAR analysis. After the analysis is carried out, a work program (proker) is prepared which is adaptive in the community. The work program successfully launched by the third generation of STIBA Makassar KKN students in Mangeloreng Village is socialization and friendship (SS), TK / TPA inauguration, TK / TPA inauguration, elementary / junior high school teaching, Arabic language learning group (KBBA), Santri festival (FS) ), and dirosa learning (PD). The results of the implementation of this Community Service program are that the interest and enthusiasm of the children (santri) has progressed in learning the Qur'an, religious knowledge, and Arabic. This can be marked by the increase in the number of students studying Koran at the TPA, the Arabic learning group and the inauguration of 1 new TPA, as well as the support of parents of students who fully appreciate the educational programs of STIBA Makassar KKN students. The development of the Koran skills was also seen in the adult al-Qur'an study group (Dirosa), the markers were proficiency in the recitation of Makhraj and Tajweed.